Antecedents of customer WOM in glamping: The critical role of original ecology. (May 2021) - Lu, Jiandong; Wang, Xiaolei; Dai, Zheng; Chen, Guo; Feng, Yuqiang
Highlights: Original ecology includes authenticity, scenery and natural lifestyle. Customers' emotional value includes enjoyment, tension release and social bonding. Different dimensions of original ecology can affect customers' emotional value. Room and public space of the accommodation can affect customers' emotional value. Customers' emotional value in glamping can affect their WOM. Abstract: Glamping has grown increasingly popular as a new type of outdoor hotel that combines nature with luxury. Glamping operations managers must fully understand how certain attributes of their business affect their customers' word-of-mouth (WOM) in order to sustain growth and attract new customers. There has been little previous research on the influence of nature-related attributes on customers' emotions and WOM. To address this gap, we conducted interviews in two glampsites based on the Stimulus-Organism-Response (SOR) framework. We also analyzed online reviews for 20 glampsites. We conducted qualitative analysis on the data using grounded theory techniques. We found that original ecology (including authenticity, scenery, and natural lifestyle) and accommodation environment (including room and public space) can affect customers' emotional value (including tension release, enjoyment, and social bonding), which can in turn affect their WOM. The results presented here may provide useful implications for both researchers and glamping business managers.